Nilai-nilai Moral pada Cerpen Pelajaran Mengarang Karya Seno Gumira Ajidarma serta Implikasi terhadap Pembelajaran Bahasa Indonesia di SMP - Aripin, Enjen Zaenal; Asuti, Tri; Suhardjono, Dadi Waras (Medan Resource Center, 2024)
In this thesis the author discusses the Moral Values in Short Stories Composing Lessons by Seno Gumira Ajidarma and the Implications for Language Learning in Indonesian Middle Schools. This research aims to describe the form of conveying moral values in the short story